LEARNING MODEL DEVELOPMENT OF TEAMS-GAMES-TOURNAMENTS (TGT) IN LEARNING GERMAN VOCABULARY (WORTSCHATZ) FOR SENIOR HIGH SCHOOL STUDENTS IN MAKASSAR - Usman, Misnawaty; Saud, Syukur; Achmad, Abdul Kasim (Universitas Negeri Makassar, 2018)
The purpose of this study was to develop a learning model of Teams-Games-Tournaments (TGT) in learning German vocabulary (Wortschatz). Specifically the study aims: (a) to find out the validity, practicality, and effectiveness of German vocabulary learning to improve students' vocabulary mastery; (b) to find out the effectiveness Teams-Games-Tournaments (TGT) learning model for German vocabulary learning. The subjects of this study were teachers and students of class XI at SMA 11 Makassar. The data were collected via implementation of learning model sheet, questionnaire, and test. Learning model development of this study was examined in terms of validity and effectiveness. Learning model development was designed using 4-d procedures; defining stage, design stage, development stage, and disseminate stage. The result showed that learning model of Teams-Games-Tournaments (TGT) in learning German vocabulary (Wortschatz) was valid, practical and effective. The validity of this model was; learning implementation plans (3.86), textbooks (3.58), student’s worksheets (3.78), and teachers' handbook (3.84). By using t- test formula where th (10,128) > tt (2,002) with alpha level (α) 0,05, showed the learning model of Teams-Games-Tournaments (TGT) was effective in learning German vocabulary.